Pengaruh Peran Guru terhadap Pengasuhan Anak Usia 3-5 Tahun di TPA Siti Hajar Kota Gorontalo - Elva M. Sumirat; Nur Cynthia Roman; Aida Insani Azzahra; Sri Lestari Zainudin; Marsha S. Daud; Nurfazria Y. Kaharu; Fauzia H. Minura (Inovasi Pendidikan dan Anak Usia Dini, 2026)
This study aims to understand and explain in depth the role of teachers in the care of children aged 3–5 years at the Siti Hajar Kindergarten and its influence on child development. This study used a qualitative approach with the aim of obtaining a comprehensive picture of the interactions between teachers and children in daily care activities. Data were obtained through observation, interviews, and documentation that describe care practices in the TPA environment. The results show that teachers have a very important role, including as guides in learning activities, mediators in children's social and emotional development, motivators to foster interest in learning, role models of positive behavior, and communication bridges between children and parents. These roles contribute significantly to character formation, social skills development, increased learning motivation, and children's emotional well-being. Despite facing various obstacles, such as limited facilities and challenges in maintaining children's concentration, teachers continue to strive to provide optimal care through enjoyable learning strategies and active communication with parents. This study recommends increasing teacher capacity and strengthening collaboration between educational institutions and families to support the sustainable growth and development of early childhood.